Analysis of the anomie behavior and external motivation of college students in sports: A cross-sectional study among gender - Liu, Liping; Chen, Shanping; Yang, Xueyan (Frontiers in Psychology, 2022)
Objective: In the context of Healthy China, the effect of external motivation on sports anomie behaviour from the perspective of gender among Chinese college students was investigated. Participants: 2340 college students. Methods: The self-made scales were used which were about anomie behaviour and external motivation in sports. The independent sample T-test compared sports anomie behaviour between male and female students. Then Multiple linear regression analysis was adopted to examine the effects of external motivation on sports anomie behaviour. Results: Girls’ sports anomie behaviour was lower than boys. There were significant gender differences in honour motivation, obedience motivation, and economic motivation; girls’ motivations were lower than boys. The academic motivation was negatively correlated with sports anomie behaviour for college students of both genders. The economic motivation was positively correlated with their sports anomie behaviour. Honour motivation was negatively correlated with the sports anomie behaviour of female college students. Conclusion: Female college students' sports anomie behaviour and external motivation are lower than that of male college students. External motivation had a significant influence on college students' sports anomie behaviour.